Theoretical Basis of Improving the Methodology of Developing the Creative Competence of Future Specialists in Preschool Educational Organizations - Saydullaeva Nargis Ilhom qizi (International Journal on Integrated Education, 2021)
This article describes the creative qualities of future professionals in preschool education, the theoretical basis for improving the methodology of developing creative competence.